David T. Mitchell y Sharon L. Snyder (2015): The biopolitics of disability. Neoliberalism, Ablenationalism, and Peripheral Embodiment. Ann Arbor: University of Michigan Press - Sergio Rubio Burgos (Revista Española de Discapacidad, 2019)
Reseña de la obra 'The biopolitics of disability. Neoliberalism, Ablenationalism, and Peripheral Embodiment' (2015) de David T. Mitchell y Sharon L. Snyder.